A cooking simulation mobile application using Manomotion - Choo, Coslynn Yi Ning (Nanyang Technological University, 2021)
Childhood obesity is increasingly widespread in Singapore. While there are many factors that contribute to childhood obesity, one major cause is children’s poor diets. Many Singaporean children eat out frequently and consume unhealthy meals on a regular basis. Since children’s poor diets stem from their own personal choices, a possible solution may be to improve children’s cooking knowledge and encourage them to prepare simple and healthy meals on their own. Cooking simulation video games may be an effective tool for teaching children how to cook, but existing games in the market lack realism and interactivity. One possible solution to improve the efficacy of cooking simulation video games is by using hand tracking technology. The Manomotion SDK is one such technology and provides realtime hand tracking and gesture analysis capabilities that can be integrated into a variety of platforms such as iOS, Android and the Unity game engine. The Manomotion SDK only requires the pre-existing camera of a mobile device to work and allows users to manipulate game objects using their hand movements and gestures. This aim of this project was to design and develop a cooking simulation mobile application that offers players an immersive and realistic cooking experience. With the use of the Manomotion SDK’s hand tracking and gesture analysis features, players can use their hands as an input source to perform common food preparation and cooking actions. The application aims to promote healthy eating among children by acting as an easily accessible substitute for reallife cooking classes and improving children’s cooking knowledge.